DINAMIKA KOMUNIKASI: Telaah atas Sejarah, Perkembangan dan Pengaruhnya terhadap Teknologi Kontemporer - Efendi, Bukran (LP2M Institut Agama Islam Nurul Hakim, 2021)
Scientific epistemology has experienced dynamics along with the development of increasingly complex times, especially in the study of scientific theories as one of the scientific disciplines that is continuously studied in science. One of the most frequently discussed theories and issues is communication as an alternative to develop a better life. Logically, communication is often used as a reference for conveying information and all kinds of other fields. This is the importance of understanding communication and the flow of communication dynamics in today's era. The focus of this research examines several fundamental aspects as well as the formulation of the problem in this research, namely, How Historically and Development of Communication and its influence in the current era. The formulation of the problem serves as a basic reference to explore and examine the development and importance of communication science in a social context. Keywords, the nature of communication has an important role in the relationship between people, because communication is a basic tool for transforming information into other information, especially in establishing social relationships. Based on historical facts, communication science is not only concerned with the context of mass communication, but also the development of communication science, especially in the context of social relations.